The health impact of hazardous waste landfills and illegal dumps contaminated sites: An epidemiological study at ecological level in Italian Region - Fazzo, Lucia; Manno, Valerio; Iavarone, Ivano; Minelli, Giada; De Santis, Marco; Beccaloni, Eleonora; Scaini, Federica; Miotto, Edoardo; Airoma, Domenico; Comba, Pietro (Frontiers in Public Health, 2023)
Background and aim The implementation of idoneous management of hazardous waste, in contrast to illegal practices, is one of the environment and health priorities of the WHO. The aim of the present study, based on a collaborative agreement between the Italian National Health Institute and a Prosecution Office located in Naples North, was to evaluate the health effects of illegal landfills and burning of urban and hazardous waste in the territory of the Prosecution Office. Methods The municipalities included in the study territory were investigated with respect to the regional population. Regression analyses were performed in the study area between four classes of an environmental municipal indicator of waste risk (MRI) previously defined, computing the relative risks (RRs) in 2–4 MRI classes, with respect to the first MRI class (the least impacted). The prevalence of reproductive outcomes and cause-specific mortality and hospitalization were analyzed in the general population and in the 0–19-year-old population using SAS software. Results An increase of mortality and hospitalization risk in both the genders of the whole area, with respect to regional population, were found for overall all cancer cases, cancer of the stomach, the liver, the lung and the kidney, and ischemic heart diseases. An increase of mortality for leukemias in the 0-19-year-old population and in hospitalization risk for certain conditions originating in the perinatal period were observed. Correlation between MRI and the risk of mortality from breast tumors in women (MRI class 2: RR = 1.06; MRI class 3: RR = 1.15; MRI class 4: RR = 1.11) and between MRI and the risk of hospitalization from testis tumors (MRI class 2: RR = 1.25; MRI class 3: RR = 1.31; MRI class 4: RR = 1.32) were found. The hospitalization risk from breast tumors and asthma exceeded significantly in both genders of three and four MRI classes. Among the 0-19-year-old population, correlation between MRI and hospitalization from leukemias (MRI class 2: RR = 1.48; MRI class 3: RR = 1.60; MRI class 4: RR = 1.41) and between MRI and the prevalence of preterm birth (MRI class 2: RR = 1.17; MRI class 3: RR = 1.08; MRI class 4: RR = 1.25) were found. Conclusion A correlation between health outcomes and the environmental pressure by uncontrolled waste sites was found. Notwithstanding the limitation of the study, the results promote implementing the actions of environmental remediation and the prosecution of illegal practices.